2016
DOI: 10.1140/epjc/s10052-016-4352-x
|View full text |Cite
|
Sign up to set email alerts
|

How the dark energy can reconcile Planck with local determination of the Hubble constant

Abstract: We try to reconcile the tension between the local 2.4 % determination of Hubble constant and its global determination by Planck CMB data and BAO data through modeling the dark energy variously. We find that the chi-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 29 publications
1
59
0
Order By: Relevance
“…It is important to stress that w is strongly correlated with H 0 ; see the triangular plots in Appendix B. More precisely, the high value of H R18 0 pushes w towards (somehow troubling) phantom values; in other words, the wCDM model can alleviate the tension between global and local determination of the Hubble constant [1, 11,16].…”
Section: B Wcdm Parametrizationmentioning
confidence: 99%
“…It is important to stress that w is strongly correlated with H 0 ; see the triangular plots in Appendix B. More precisely, the high value of H R18 0 pushes w towards (somehow troubling) phantom values; in other words, the wCDM model can alleviate the tension between global and local determination of the Hubble constant [1, 11,16].…”
Section: B Wcdm Parametrizationmentioning
confidence: 99%
“…This could bring the Planck constraint into better agreement with higher values of the Hubble constant. By varying both parameters simultaneously, it has been shown that there is no privilege for dark radiation if allowance is made for dynamical dark energy Di Valentino et al (2016bValentino et al ( , 2017b; Huang & Wang (2016); Zhao et al (2017). Phantom energy can be shown to also ameliorate the age conflict Cepa (2004).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the extra effect of the tension on cosmological models, we consider the additional parameter N eff in the cosmological model because the addition of the parameter N eff is considered to be a good scheme to relieve the tension between the direct H 0 measurement and the Planck observation [23,24,[46][47][48][49][50]. In fact, in the literature it is shown that the tension could also be relieved to some extent by considering a dynamical dark energy [51][52][53][54][55] or light sterile neutrinos [47,48,[56][57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%